Dynamic service analytics capabilities and service firm performance: Exploring the mediating roles of adaptive and customer-linking capabilities - Yanting Huang; Kai Zhang; Xuejiao Chen (PLoS ONE, 2026)
Although service firms use dynamic service analytics capabilities (DSAC) to respond to dynamic customer demands, how these capabilities translate into performance remains unclear. Based on a sample of 338, this study explores the effects of DSAC on firm performance and the chain mediating roles of adaptive and customer-linking capability. The results reveal that DSAC enhance performance; adaptive capability partially mediate between DSAC and firm performance; adaptive capability partially mediate between DSAC and customer-linking capability; and customer-linking capability partially mediate between adaptive capability and firm performance. Adaptive and customer-linking capabilities form a continuous mediating path through which DSAC enhance service firm performance. The findings not only enrich the existing research on the relationship between DSAC and firm performance, but also provide an actionable path for service firms to enhance the effectiveness of DSAC, helping practitioners to be more flexible in responding to market changes.